2017
DOI: 10.1007/s00213-017-4707-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in N2 amplitude in response to deviant drug-related stimuli during a two-choice oddball task in long-term heroin abstainers

Abstract: Rationale Chronic heroin use can cause deficits in response inhibition, leading to a loss of control over drug use, particularly in the context of drug-related cues. Unfortunately, heightened incentive salience and motivational bias in response to drug-related cues may exist following abstinence from heroin use.Objectives The present study aimed to examine the effect of drug-related cues on response inhibition in long-term heroin abstainers.Methods Sixteen long-term (8-24 months) male heroin abstainers and 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Moreover, chronic opioid use and opioid dependence are associated with diminished cognitive control functions, including deficits in response inhibition [16][17][18][19], which can persist beyond cessation of and withdrawal from opioid use [20,21]. Opioid-dependent individuals exhibit attenuated inhibitory control-related fMRI BOLD signal in medial prefrontal circuitry, including the anterior cingulate cortex [22,23] and medial prefrontal cortex [24], and have worse behavioral performance compared with nonopioid-dependent persons across a broad range of task probes of response inhibition including the arrow task [25], the standard Go/NoGo task [22], and the affective Go/NoGo task [26].…”
Section: Opioid Use and Response Inhibitionmentioning
confidence: 99%
“…Moreover, chronic opioid use and opioid dependence are associated with diminished cognitive control functions, including deficits in response inhibition [16][17][18][19], which can persist beyond cessation of and withdrawal from opioid use [20,21]. Opioid-dependent individuals exhibit attenuated inhibitory control-related fMRI BOLD signal in medial prefrontal circuitry, including the anterior cingulate cortex [22,23] and medial prefrontal cortex [24], and have worse behavioral performance compared with nonopioid-dependent persons across a broad range of task probes of response inhibition including the arrow task [25], the standard Go/NoGo task [22], and the affective Go/NoGo task [26].…”
Section: Opioid Use and Response Inhibitionmentioning
confidence: 99%
“…In contrast, however, former OUD and cocaine users display no N200 differences from non-users during response inhibition tasks involving neutral and emotional stimuli (114). OUD users abstinent at least 1 month show greater N200 amplitude to opioid images during a dot probe task than controls (115), in contrast, OUD users abstinent 8–24 months exhibit smaller N200 to opioid images than healthy subjects (108). These results suggest that addicted individuals experience inhibitory difficulties in the presence of drug cues as represented by the Preoccupation/Anticipation stage of addiction that may change as a function of prolonged recovery.…”
Section: Framing Oud Research Within the Neurocircuitry Of Addictionmentioning
confidence: 98%
“…Moreover, neuroimaging studies have further demonstrated that, relative to healthy groups, heroin addict groups exhibit abnormal structures and lower levels of activation in brain regions related to inhibitory control during the Go/No-Go task, including impairments in the bilateral medial prefrontal gyrus, bilateral anterior cingulate cortex (ACC), dorsolateral prefrontal cortex (DPFC), left middle frontal gyrus (MFG), and left insular and bilateral inferior frontal gyrus (IFG) (Fu et al, 2008;Luijten et al, 2014;Moningka et al, 2018). Inhibitory control failure and associated brain dysfunction are key underlying factors of relapse and addiction (Su et al, 2017). Therefore, inhibitory control may be an important factor related to aerobic exercise in reducing the risk of relapse in heroin addicts.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of electroencephalogram (EEG) studies have characterized inhibitory control dysfunction in heroin addicts using event-related potentials (ERPs) associated with the Go/No-Go task (Morie et al, 2014;Steele et al, 2014;Yang et al, 2015;Su et al, 2017). These studies have shown that the N2 component is sensitive in measuring the dysfunction of heroin addicts under No-Go conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation